Atividades sobre progressões aritméticas através do reconhecimento de padrões - Mantovani, Haroldo (Universidade Federal de São Carlos, 2015)
The importance of the development of sequences that are arithmetic progressions in the high school was observed in learning situations which the students could investigate and identify patterns in numerical and geometric sequences, building the algebraic language to describe them. This work contributes for the student to build the idea of algebra as language to express irregularities, that is one of the proposed issues by the National Curricular Parameters (PCNs) for the math teaching in the fourth cycle of high school, which contrasts, nowadays, with the scarcity of activities involving observed arithmetic progressions in at least twelve years of experience as a math teacher in these cycles. The elaboration of a teaching product, in the way of activity sheets that, through the recognizing of numerical and geometric patterns, takes the student to the comprehension of the concept of arithmetic progression which could be tested through the application of these activity sheets in two classrooms of the ninth year of high school in a public municipally school. The obtained results of these applications were analyzed and compared to the previous analyzes in raised hypothesis during the elaboration of the activity sheets, using, as investigation methodology, the Didactic Engineering. The students did the activities in groups of two or three, were well motivated and participated as principal character during the application of all steps proposed in the paper, which guaranteed the good development of the activity. In according to the evaluation learning, the students reaching the proposed goals and noting that the produced teaching material works. It is believed that the elaborated material can be useful for other teachers who want to develop, in their classes, arithmetic progressions through the recognizing of patterns, adapting it to the reality of their classrooms. This work contributes hugely to the author, bringing a big professional evolution that starts with the issue choice, continued in the elaboration of the didactic sequence and the application of the activity sheets and finished with the reflection of what have been done and is registered here.
Keywords: Progressões Aritméticas; Reconhecimento de padrões; Sequência Didática; Folhas de Atividades; Arithmetic Progressions; Patterns Recognizing; Didactic Sequence and Activity Sheets; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA::ANALISE NUMERICA